2017
DOI: 10.1186/s13756-017-0184-1
|View full text |Cite|
|
Sign up to set email alerts
|

Candidemia in a major regional tertiary referral hospital – epidemiology, practice patterns and outcomes

Abstract: BackgroundCandidemia is a common cause of nosocomial bloodstream infections, resulting in high morbidity and mortality. This study was conducted to describe the epidemiology, species distribution, antifungal susceptibility patterns and outcomes of candidemia in a large regional tertiary referral hospital.MethodsA retrospective surveillance study of patients with candidemia was conducted at Singapore General Hospital between July 2012 and December 2015. In addition, incidence densities and species distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 28 publications
3
21
4
Order By: Relevance
“…Several studies,have indicated that resistance to echinocandins has increased 4 27 28. These findings are in accordance with our results.…”
Section: Discussionsupporting
confidence: 94%
“…Several studies,have indicated that resistance to echinocandins has increased 4 27 28. These findings are in accordance with our results.…”
Section: Discussionsupporting
confidence: 94%
“…Our multivariable analysis determined both neutropaenia and neutrophilia to be the clinical predictors of candiduria with candidaemia. Retrospective analyses found that neutropaenia was present in 8%‐11.6% of patients diagnosed with candidaemia . In comparison, neutropaenia was present in 8.7% of our patient population.…”
Section: Discussionmentioning
confidence: 63%
“…Retrospective analyses found that neutropaenia was present in 8%-11.6% of patients diagnosed with candidaemia. 31,32 In comparison, neutropaenia was present in 8. In regard to antibiotics, we found β-lactam/β-lactamase inhibitors to be significantly associated with elevated rates of candidaemia in candiduric patients.…”
Section: Discussionmentioning
confidence: 95%
“…Among 231 non-albicans Candida isolates, fluconazole resistance and dose-dependent susceptibility were reported in 15 (6.49%) and 41 (17.7%), respectively (P < 0.001). The increase in non-albicans Candida infection, which is considered to be due to the increased use of fluconazole, has been reported in several studies (Diekema et al, 2012;Teo et al, 2017). Empirical or preemptive echinocandin therapy is preferred especially in critically ill patients who are at risk of exposure to azole or colonization of azole-resistant species (Cornely et al, 2012;Pappas et al, 2016).…”
Section: Discussionmentioning
confidence: 99%